Selected aspects of job motivation as seen by EFL teachers - Łęska-Drajerczak, Iwona (Glottodidactica, 2000)
The article presents a preliminary report of 120 questionnaires addressed at EFL teachers and distributed between 1998-2000. The survey aims at obtaining information on the condition of teacher job motivation at the present stage of their professional career and determining the factors which are positive job motivators and those which are negative job motivators as described by EFL teachers. The article presents a brief description of 6 selected questions and the interpretation of obtained results. The survey is part of a Ph.D. dissertation entitled „Motivation and Self-Perception of EFL teachers”.